Pengaruh Variasi Kecepatan Udara Terhadap Fuel Convertion rate Insenerator Fluidized Bed Oxy-Fuel Limbah Medis dengan Bed Material Pasir Alumina - Sitorus, Chrisbiantoro Saverius; Winaya, I N Suprapta; Wijaksana, Hendra (Teknik Desain Mekanika; Vol 10 No 3 (2022): Juli 2022 : Teknik Desain Mekanika, 2022)
Abstract The case of medical waste especially caused by the increasing number of medical waste during the COVID-19 period, resulting in a surge in medical waste. The method in processing B3 waste is the thermal process method. The thermal process (incineration) is one of the alternative technologies in the process of treating B3 waste. B3 waste treatment uses the incineration method. The addition of Oxy-fuel in combustion aims to expect exhaust gas emissions to be dominated by CO2 gas so as to facilitate the process of capturing CO2 gas. The oxy-fuel environment is very different from the air environment. The combustion efficiency at each air velocity variation is different but not so significant, which is caused by the fluidization ability of each different air velocity which results in the bed material's ability to distribute and maintain different heat, so the LHV value of the flue gas produced is also different. The result of this research is that the speed of 4 m/s is recorded as having the highest fuel conversion rate of other air velocity variations, namely 1,982 kg/hour and also the speed of 4 m/s with alumina sand bed material also able to fluidize well. Keywords: medical waste, incinerator, air velocity, fuel conversion rate